(untitled) (Bangladesh Journal of Child Health, 2017)
Advances in technology and training in paediatric cardiology have improved longterm outcome and promised better quality of life. Bangladesh is facing multitude of health problems and congenital heart disease is one of them. With facilities for accurate diagnosis and scope of complete correction, more and more children are undergoing cardiac intervention and surgical treatment for congenital heart diseases. So there is increasing demand for dedicated personnel for the specialized intensive care of these critically ill children. A dedicated team dictating specialized intensive care has translated into better outcomes in several centers. Over recent decades, specialized paediatric cardiac intensive care has emerged as a central component in the management of critically ill neonatal and paediatric patients with congenital and acquired heart disease worldwide. The majority of developed centers have dedicated paediatric cardiac intensive care units to care for paediatric cardiac patients. In developing countries with limited resources, pediatric cardiac intensive care is yet to take root as a distinctive discipline. Congenital heart surgery, together with transcatheter interventions, has resulted in marked improvement in cardiac care in Bangladesh. So, we need to establish more and more dedicated paediatric cardiac center and cardiac intensive care units to care for paediatric cardiac patients. Bangladesh J Child Health 2015; VOL 39 (3) :141-147